Pengaruh Kompetensi Dan Independensi Auditor Terhadap Kualitas Audit - Nur Rohmawati; Tumirin Tumirin (Pusat Riset dan Inovasi Nasional, 2023)
The aim of the research is to analyze the influence of auditor competence and independence on audit quality. This type of research is quantitative research by distributing questionnaires. The theory used in this research is attribution theory. The sampling method in this study was purposive sampling method. The sample used in this study was 57 respondents. The analytical method used is multiple linear regression analysis. The results of this research indicate that the auditor competency variable has a significant effect on audit quality and auditor independence has a significant effect on audit quality. This can encourage or improve audit quality.